Isothermal DNA amplification coupled to Au-nanoprobes for detection of mutations associated to Rifampicin resistance in Mycobacterium tuberculosis - Veigas, Bruno (2013)
We acknowledge Fundacao para a Ciencia e a Tecnologia (FCT-MCTES) for financial support CIGMH (PEst-OE/SAU/UI0009/2011); Projects PTDC/BBB-NAN/1812/2012, PTDC/CTM-NAN/109877/2009; SFRH/BD/78970/2011 for BV. PVB thanks Santander-Totta/UNL for financial support (Scientific Prize Edition 2012).